A case report of eosinophilic cystitis complicated with transient vesicoureteral reflux - Ogura, H (Hinyokika kiyo. Acta urologica Japonica, 1991)
A case of eosinophilic cystitis complicated with transient vesicoureteral reflux in an 11-year-old girl with allergic disorders is reported. She was suffering from pollakisuria, painful urination, vesical irritability, and gross hematuria for about 2 months. Urinalysis showed aseptic pyuria. White blood cell count was 9,700/mm3 with eosinophils of 10%. Eosinophils were also found on urine cytology. Intravenous pyelography revealed bilateral hydronephrosis and apparently contracted bladder. Tumorous lesion and edematous mucosa were observed in the retrotrigonal region on cystoscopy. The multiple bladder biopsy uniformly revealed eosinophilic cystitis. Following antiallergic treatment, practically all symptoms subsided in steps, and normal cystoscopic appearance and histological structure were restored in 3 months. The vesicoureteral reflux markedly diminished in 10 months